Evaluation and management of blepharoptosis - Cohen, Adam J.; Weinberg, David A.; SpringerLink (Online service). (New York Springer, 2011)
This comprehensive and detailed text deals with the diagnosis and surgery of blepharoptosis, and will benefit any practicing physician, fellow or resident who deals with blepharoptosis.
Muller's muscle-conjunctival resection (posterior approach) -- Open-sky (anterior approach) Muller's muscle resection for the correction of blepharoptosis -- The Fasanella-Servat procedure for ptosis -- Full-thickness eyelid resection for blepharoptosis correction -- Frontalis suspension for the correction of blepharoptosis -- In-office surgery, anesthesia, and analgesia -- Ethnic and gender considerations in ptosis surgery -- Aesthetic considerations for the ptosis surgeon -- Challenging ptosis scenarios -- Ptosis surgery: comparing different surgical techniques -- Ptosis surgery failure and reoperation -- Complications of ptosis repair: prevention and management -- Commentary: perspective of a risk manager: 12 steps of a successful surgical encounter.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Blepharoptosis; Blepharoptosis -- diagnosis; Blepharoptosis -- therapy; Blepharoplasty -- methods; Electronic books